Sibirskoi gosudarstvennoi akademii fizicheskoi kul'tury - 50 let - Mikhalev, V. I. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
This article is devoted to the 50-th anniversary of Siberian state academy of physical culture. The main historical stages of the academy development are represented. The author noted a wide rank of outstanding people, which made a noticable contribution to the academy's professional, sports and scientific fame. Special attention had been paid to the main tendencies of the academy's scientific life. Some theoretical and methodical researches conducted by the institute scientists had been noted. Above that, the author described some developmental perspectives oriented to the improvement of student's professional training, sports mastership perfection, further reformation of educational process.